Sustaining immunity during starvation in bivalve mollusc: A costly affair. Issue 2 (April 2017) - Mahapatra, Elizabeth; Dasgupta, Dishari; Bhattacharya, Navodipa; Mitra, Suvrotoa; Banerjee, Debakana; Goswami, Soumita; Ghosh, Nabanita; Dey, Avijit; Chakraborty, Sudipta
Highlights: Innate immunity of the freshwater bivalve mollusc was studied under starvation. The bivalve maintained homeostasis in haemocyte mediated PI and nitrite generation during stress. The α-amylase activity and protein content in haemolymph and tissues were least affected. Histopathology revealed that the bivalve incurred degeneration of its own tissue reserves. Study indicates the adaptive immune behaviour of the bivalve during nutrient limited condition. Abstract: Complete or partial depletion of resource in a freshwater habitat is a common phenomenon. As a consequence, aquatic fauna including bivalve molluscs may be exposed to dietary stress on a seasonal basis. Haemocyte based innate immune profile of the freshwater mollusc Lamellidens marginalis (Bivalvia: Eulamellibranchiata) was evaluated under starvation induced stress for a maximum period of 32 days in a controlled laboratory condition. During starvation, the bivalve haemocytes maintained a homeostasis in phagocytic efficacy and nitric oxide generation ability with respect to the control. The mollusc maintained a significantly high protein content in its haemolymph and tissues under the nutritional stress with respect to the control. The dietary stress had no significant impact on the activity of digestive tissue derived α-amylase till sixteenth day but by 32 days the enzyme activity went down significantly. The histopathological profile revealed that the bivalve was adapted to maintain a steady immune profile by incurring degeneration of its own tissue structure. The total haemocyte count surged significantly till 16 days but differed insignificantly with respect to the control at 32 days implying probable haematopoietic exhaustion. The study reflects the instinctive urge of the bivalve to maintain immune physiology at heavy metabolic cost under nutrient limited condition.